Effect of different organic manures and salinity levels on greenhouse gas emission and growth of common carp in aquaculture systems. (21st December 2020) - Naskar, Sanchita; Pailan, Gour Hari; Datta, Subhendu; Banerjee Sawant, Paramita; Bharti, Vidya Shree
Abstract: A study was conducted to evaluate the effect of three different organic manures and salinity levels on production of greenhouse gases (GHGs) and their interactive effects on growth and physiological parameters of common carp ( Cyprinus carpio ) in peri‐urban aquaculture tank system. The experiment had 3 × 3 factorial design with three types of organic manures, that is humic acid, FMGY (fermented boiled rice, molasses, groundnut oil cake and yeast) and cow dung tested in combination with three different salinity levels, that is 0.2, 2.5 and 5.0 g/L in triplicates. C. carpio fingerlings (average weight and length of 7 g and 7.15 cm respectively) were distributed to 27 number of 1000‐litre FRP tanks (nine treatments with triplicates) containing 10 fish per tank. Fish were maintained for an experimental period of 180 days with a diet containing 30% crude protein. GHG estimation was done on 120th, 150th and 180th days at 30‐day interval by collecting gaseous sample following floating chamber method. Lowest GHG emission (917.73) CO2 equivalent (mg m −2 h −1 ) was recorded in T3 treatment (humic acid + 5 g/L salinity). Highest fish growth was evident in T2 treatment (humic acid with 2.5 g/L salinity). GaSI and HSI were higher in treatment T2. Lowest stress parameters (plasma glucose and serum cortisol) were recorded in T4 treatment (FMGY with 0.2 g/L salinity). In terms of GHG emission, growth and bio‐indices in C. carpio tank rearing, humic acid is the best organic manure at less than 5 g/L water salinity.